The Effect of Chitosan Incorporation on Physico-Mechanical and Biological Characteristics of a Calcium Silicate Filling Material - Sumaya Abusrewil; J. Alun Scott; Saeed S. Alqahtani; Mark C. Butcher; Mohammed Tiba; Charchit Kumar; Daniel M. Mulvihill; Gordon Ramage; William McLean (MDPI AG, 2024)
Objectives: A tricalcium silicate-based cement, Biodentine™, has displayed antibiofilm activity when mixed with chitosan powder. This study aimed to assess the effect of chitosan incorporation on the physico-mechanical and biological properties of Biodentine™. Methods: In this study, medium molecular weight chitosan powder was incorporated into Biodentine™ in varying proportions (2.5 wt%, 5 wt%, 10 wt%, and 20 wt%). The setting time was determined using a Vicat apparatus, solubility was assessed by calculating weight variation after water immersion, radiopacity was evaluated and expressed in millimeters of aluminum, the compressive strength was evaluated using an Instron testing machine, and the microhardness was measured with a Vickers microhardness tester. In addition, surface topography of specimens was analyzed using scanning electron microscopy, and the effect of chitosan on the viability of human embryonic kidney (HEK 293) cells was measured by a colorimetric MTT assay. Results: Incorporation of 2.5 wt% and 5 wt% chitosan powder delivered an advantage by speeding up the setting time of Biodentine material. However, the incorporation of chitosan compromised all other material properties and the crystalline structure in a dose-dependent manner. The chitosan-modified material also showed significant decreases in the proliferation of the HEK 293 cells, signifying decreased biocompatibility. Significance: Chitosan incorporation into calcium silicate materials adversely affects the physical and biological properties of the material. Despite the increased antimicrobial activity of the modified material, the diminution in these properties is likely to reduce its clinical value.